Corporate reputation: The definitional landscape - Barnett, M; Jermier, J; Lafferty, B (Palgrave, 2006)
While interest in the concept of corporate reputation has gained momentum in the last few years, a precise and commonly agreed upon definition is still lacking. This paper reviews the many definitions of corporate reputation present in the recent literature and categorizes these definitions based on their similarities and differences. The purpose of the study is to review, analyze and evaluate prior definitional statements of corporate reputation. The analysis led us to conclude that the cluster of meaning that looks most promising for future definitional work uses the language of assessment and specific terms such as judgment, estimation, evaluation or gauge. Based on this review work and a lexicological analysis of the concept of reputation, we propose a new definitional statement that we think adds theoretical clarity to this area of study. The statement defines corporate reputation more explicitly and narrowly and distinguishes this concept from corporate identity, corporate image and corporate reputation capital. It is our hope that this study and the resulting definition will provoke further scholarship devoted to developing one voice when it comes to corporate reputation as a concept.